(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2023)
Workplace Bullying Institute (2021) defines this concept as "repeated mistreatment: abusive conduct that is threatening, intimidating, or humiliating; work sabotage or verbal abuse." It is estimated that around 79 million Americans are bullied at work, with 67% of them could face a job loss. Overall, 49% of working Americans were affected by bullying at work, directly or indirectly. Target’s ethnicity, age, type of employment, number of years of service, etc., played a role in the type and amount of harassment experienced. The current study explored the physiological and psychological effects of workplace bullying among employees in the United States. Data from a sample of 176 employees were analyzed for this article. (More responses are still being collected.) A 60-item questionnaire included quantitative and qualitative questions regarding demographic information, workplace culture, bullying experiences (personal and witnessed), and responses to bullying. Finally, their awareness of current policies on harassment and bullying was explored. For the present article, two important research questions will be explained – regarding (i) physiological and emotional health issues and (ii) on-the-job stress and work-life balance. Other aspects of the survey will be elaborated on in future publications. Additionally, theoretical foundations, a discussion of major findings, conclusions, and recommendations are included.